PENINGKATAN AKTIVITAS, MOTIVASI DAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPENUMBERED HEADS TOGETHER PADA SISWA KELAS IV SD NEGERI 009 SAMARINDA ULU - Siska Oktaviani (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This research is a classroom action research conducted in SDN 009 Samarinda Ulu Academic Year 2016/2017. The subjects were students of class IV of 39 students consisting of 17 male students and 22 female students. The purpose of this study to increase the activity, motivation and learning outcomes mathematics using cooperative learning type Numbered Heads Together. The experiment was conducted on three cycles, each cycle consisting of four phases: planning, implementation, observation and reflection. Data collection techniques used were observation, test and documentation with instruments such as observation sheets, a booklet and school documentation. Data activity and motivation acquired through observation, while learning outcomes data obtained through student worksheets and tests end of the cycle. Data were analyzed using the final value formula, formula and formula average percentage